Cognitive, Motor and Social Factors of Music Instrument Training Programs for Older Adults’ Improved Wellbeing - MacRitchie, Jennifer; Breaden, Matthew; Milne, Andrew J.; McIntyre, Sarah (Frontiers in Psychology, 2020)
Given emerging evidence that learning to play a musical instrument may lead to a number of cognitive benefits for older adults, it is important to clarify how these training programs can be delivered optimally and meaningfully. The effective acquisition of musical and domain-general skills by later-life learners may be influenced by social, cultural and individual factors within the learning environment. The current study examines the effects of a 10-week piano training program on healthy older adult novices’ cognitive and motor skills, in comparison to an inactive waitlisted control group. Fifteen participants completed piano training led by a music facilitator in small groups (max n=4 per lesson class; two experimental, two waitlisted control groups). Data was collected using an explanatory sequential design: quantitative data from a battery of cognitive and motor tests was collected pre/post-test on all participants, with further post-test data from the waitlisted control group (n = 7). Qualitative data included weekly facilitator observations, participant practice diaries, and an individual, semi-structured, post-experiment interview. Bayesian modelling demonstrated moderate evidence of a strong positive impact of training on part A of the Trail Making test (TMT), indicating improved visuo-motor skills. Moderate evidence for negative impacts of training on part B of the Trail Making Test (and difference score delta) was also found, suggesting no benefit of cognitive switching. Qualitative results revealed that the group learning environment motivated participants to play in musical ensembles and to socialise. Motivation was optimal when all participants were happy with the chosen repertoire (participants reported were motivated by learning to play familiar music) and when the facilitator observed that groups had formed cohesive bonds. Informed by these factors, exploratory analyses demonstrated strong evidence that a participant’s lesson class had an impact on post-test scores (TMT part A). These results not only demonstrate the extent of cognitive benefits of a short-term piano training intervention for older adults, but also the importance of considering the group dynamics in the learning environment.